Targeting the interplay of cGAS-STING and ferroptosis by nanomedicine in the treatment of cancer - Chunfei Li; Wenyan Zhao; Donghua Geng; Yuzi Jin; Wenzheng Guan (Journal of Experimental & Clinical Cancer Research)
Abstract The cyclic GMP–AMP synthase (cGAS)–stimulator of interferon genes (STING) pathway senses cytosolic DNA and triggers innate immune responses. Pharmacological activation of the cGAS-STING pathway by cGAS-STING agonists to overcome cancer drug resistance offers substantial potential to promote antitumor immunity. However, small-molecule STING agonists show rapid excretion, low bioavailability, non-specificity, and adverse effects, which limit their therapeutic efficacy and in vivo applications. The recent emergence of nanomedicine has profoundly revolutionized STING agonist delivery, promoting tumor-targeted delivery and offering new opportunities for tumor-specific immunotherapy. A growing body of evidence has shown that cGAS-STING interacts with ferroptosis in cancer cells. Targeting the interplay between cGAS-STING and ferroptosis using nanomedicines offers a novel cancer treatment regimen. In this review, we outline the principal components of the cGAS-STING signaling cascade and discuss its role in cancer biology. We also review the role of the interplay between cGAS-STING and ferroptosis in cancer genesis. We then focus on providing an overview of the latest findings and emerging concepts that leverage the interplay between cGAS-STING and ferroptosis by nanomedicine to kill cancers. Finally, we discuss the key limitations of the current therapeutic paradigm and possible strategies to overcome them. This article highlights some promising therapeutic avenues that leverage the interplay of cGAS-STING and ferroptosis by nanomedicine, which could be used to treat cancer.